EPR Analysis of Dinitrobenzoic Acid Anion Radicals - YOLBURUN, Hüsnü; UCUN, Fatih (International Journal of Computational and Experimental Science and Engineering, 2023)
EPR hyperfine coupling constants of dinitrobenzoic acid anion radicals were calculated by using (DFT) with the use of B3LYP functional at LanL2DZ, LanL2MB, EPR-II, EPR-III, 6-31+G(d) and 6-31++ G(d,p) basis sets. It was found that LanL2DZ is the best basis set from the correlation graphs between the theoretical and experimental results. Thus, in this set, the hyperfine structures formed EPR spectra and the distributions of the spin density of all the anion radicals were determined. From the optimized structures of all the radicals it was decided whether the nitro groups are out of plane or not. The reason of the different distributions of the spin density on the nitro groups were also investigated by Natural Bond Orbital (NBO) and Mulliken charge analyses. In these analyses, the interactions of the nitro groups with the ring were examined. The NBO analysis the anion radical of 2,4-dinitrobenzoic acid showed that there is a strong O-H…O hydrogen bond interaction (182.8 kcal/mol) between the carboxyl and nitro groups. The simulated EPR spectra of some radicals obtained by EPR Simulator software program were harmoniously given with together their experimental spectra.